The Life of Daily Boarding School Students: Challenges and Interventions/ Kehidupan Murid Asrama Harian: Cabaran dan Tindakan Mengatasinya (Sains Humanika, 2025)
Life in daily boarding schools offers structured learning opportunities and residential facilities for students who live far from school. However, it also presents challenges that may affect students’ emotional, social and academic well-being. This study aims to explore the challenges faced by secondary school daily boarding students in Malaysia and the actions they take to address these challenges. This study used a qualitative approach involving a total of 87 students from a daily boarding school in Iskandar Puteri, Johor. Data were collected through open-ended questions and analysed thematically. Findings revealed four main areas of challenge faced by the students: restrictive hostel rules, inadequate facilities, self-management pressures and emotional strain caused by homesickness. Students reported various coping strategies including self-regulation, seeking social support, engaging in spiritual practices and managing emotions. The study highlights the need for school and hostel administrators to incorporate students’ perspectives into policy development and facility planning to foster a more supportive and conducive living environment.
Keywords: Daily boarding school, wellbeing, challenges, homesick, students